Повесть о рыжей девочке: [повесть] / Л. Будогоская - Будогоская Лидия Анатольевна (Память Сарапула, 2005)
Экземпляры: аб. (20230921) / Инвентарный номер: 63848 / Цена: / Сис.шифр: 84(2Рос=Удм)6-4 / Авт.знак: Б 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44